PERAN PUBLIC RELATIONS DAN EDITOR & PRODUCTION DESIGN DALAM KAMPANYE "TERBUKA UNTUK SEMUA, BERGERAK BERSAMA WARGA #KULIKDIPORTALSAMAWA" SEBAGAI UPAYA BRAND COMMUNICATION UNTUK MENINGKATKAN BRAND AWARENESS SERTA USER PORTAL SEMARANG SATU DATA DAN SAMAWA (SEMUA DATA UNTUK WARGA) - Sixtwomega Aprieisa; Hapsari Dwiningtyas Sulistyani (Interaksi Online, 2026)
The Statistics Division of the Department of Communication and Informatics of Semarang City faced low public brand awareness of the Portal Semarang Satu Data and SAMAWA (Semua Data Untuk Warga) services, resulting in suboptimal utilization of public data services. This project aimed to increase brand awareness and the number of users through the implementation of an Integrated Marketing Communication (IMC) strategy encompassing public relations, direct marketing, and event marketing under the campaign “Terbuka untuk Semua, Bergerak Bersama Warga #KulikDiPortalSAMAWA.” In its implementation, Public Relations was responsible for managing communication with stakeholders and partners, while the Editor & Production Design role focused on content production and maintaining visual identity consistency across communication channels. The results showed an increase in brand awareness of Portal Semarang Satu Data by 30.8% (reaching 80%) and SAMAWA by 62.7% (reaching 75%). The number of portal users increased by 35.2% or 127,242 visitors compared to November 2025, and 19 data requests were submitted. These findings indicate that the integrated communication strategy was effective in enhancing brand awareness and public participation in Semarang City’s public data services.